Synthesis of Phenylcarbamic Acid and 2-[2-Oxo-3-(4-substituted phenylimino)-indolin-1-yl]acetohydrazide Derivatives as Promising Antifungal Agents - Al Marhoon, Zainab; Abdel-Megeed, Ahmed; N. Sholkamy, Essam; Rafiq H. Siddiqui, M.; El-Faham, Ayman (Asian Journal of Chemistry, 2014)
Four phenylcarbamic acid methyl ester derivatives were prepared by oxidative transformation of isatin's Schiff bases (Baeyer-Villiger oxidation) under conventional heating as well as microwave irradiation. The ester derivatives were treated with hydrazine hydrate under microwave irradiation to afford the hydrazide derivatives in less reaction time and good yield. 2-(2-Oxo-3-(4-substituted phenylimino)indolin-1-yl)acetohydrazide derivatives were also prepared from isatin's Schiff bases under microwave irradiation in less reaction time and high yield and purity. The synthesized compounds exhibited promising antifungal activity particularly against the human pathogenic Candida albicans. While they did not show any activity against the Streptococcus pyogenes, Staphylococcus aureus, Salmonella typhi, Klebsiella pneumoniae, Pseudomonas aeruginosa, Aspergillus flavus and Aspergillus niger.